1999
DOI: 10.1002/(sici)1096-9918(199908)28:1<119::aid-sia631>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

EIS and XPS study of the corrosion of carbon steel in inhibited natural seawater

Abstract: Electrochemical and surface analytical techniques were used to study the corrosion behaviour of a carbon steel in inhibited seawater. Linear polarization resistance and Tafel polarization measurements showed the effect of inhibitor injection on the corrosion rate of carbon steel in natural seawater. A 90% reduction in the corrosion rate was observed for the steel under investigation. In situ electrochemical impedance spectroscopy (EIS) measurements indicated that the inhibiting film formed in seawater was stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This has for example been demonstrated on carbon steel exposed to sea-water. 96 A 3dimensional structure of a lm was studied. Since an iron peak was absent at the spectrum, it was suggested that substrate was fully covered with corrosion products.…”
Section: Conventional Characterization Techniquesmentioning
confidence: 99%
“…This has for example been demonstrated on carbon steel exposed to sea-water. 96 A 3dimensional structure of a lm was studied. Since an iron peak was absent at the spectrum, it was suggested that substrate was fully covered with corrosion products.…”
Section: Conventional Characterization Techniquesmentioning
confidence: 99%
“…Whilst these certainly have great advantages (for example, electrochemical methods often allow a simple way of quantifying the corrosion of each system), they are limited in the extent to which they can provide fundamental structural information about the corroding interface. Techniques such as X-ray photoelectron spectroscopy (XPS) 38,39 have been used to better understand the surface chemistry of corroding surfaces, and whilst these are mainly ex situ, the increasing popularity of new near-ambient XPS techniques makes this a promising tool for future study in this area.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were carried out using Biologic SP-150 electrochemical workstation against open circuit potential. The EIS data were then fitted and analysed using the EC-lab software [14,[16][17][18]].…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%